39 Onset of Flibanserin Treatment Effect in Postmenopausal Women Assessed by Subdomain Scores of the Female Sexual Function Index (FSFI). Issue 1 (1st April 2022) - Simon, J; Shapiro, M; Larkin, L; Kim, N; Patel, S; Kingsberg, S
ABSTRACT: Introduction: Flibanserin, a treatment for acquired, generalized hypoactive sexual desire disorder (HSDD), is approved in the US for use in certain premenopausal women and in Canada for use in both premenopausal and naturally postmenopausal women ≤60 years of age. Improvement in symptoms following initiation of flibanserin may take several weeks to emerge and it is important to set realistic expectations of treatment onset. Objective: The primary objective of this analysis was to evaluate the onset of flibanserin's treatment effect in naturally postmenopausal women with HSDD across the 6 subdomains of the FSFI. Methods: A post-hoc analysis was conducted using FSFI data from a randomized, controlled, double-blind trial of flibanserin in naturally postmenopausal women with HSDD that included 895 postmenopausal women (flibanserin, n=432; placebo, n=463) who had at least one on-treatment efficacy assessment. The FSFI is a validated, 19-item self-report questionnaire comprising 6 subdomains of sexual functioning: desire, arousal, lubrication, orgasm, satisfaction, and pain. Each subdomain has a maximum score of 6 and higher scores indicate better sexual functioning. For each subdomain, change from baseline at each assessment visit (4, 8, 16, and 24 weeks) was calculated as the least squares mean difference. Comparisons between flibanserin and placebo groups were performed using analysis of covariance. Results: Postmenopausal patients treated with flibanserin had significantly greater sexual desire and arousal scores than those treated with placebo at Week 4 and at every assessment timepoint thereafter (see figure). By Week 8, patients in the flibanserin group had significantly higher scores for all FSFI subdomains compared to the placebo group. This treatment effect was maintained at Week 24 for all subdomains except for pain. Conclusions: Results from this post-hoc analysis indicates that postmenopausal women treated with flibanserin experienced improved sexual function compared to those treated with placebo with regard to sexual desire, arousal, lubrication, orgasm and satisfaction. This improvement was maintained over the entire course of treatment. These findings are consistent with those from a previous FSFI post-hoc analysis of clinical trial data from premenopausal women and suggest that flibanserin treatment of postmenopausal women was associated with improvement of multiple aspects of sexual function in addition to sexual desire. Disclosure: Yes, this is sponsored by industry/sponsor: Sprout Pharmaceuticals, Inc. Clarification: Industry initiated, executed and funded study Any of the authors act as a consultant, employee or shareholder of an industry for: Sprout Pharmaceuticals, Inc.